Complex EGFR mutations with secondary T790M mutation confer shorter osimertinib progression-free survival and overall survival in advanced non-small cell lung cancer. (July 2020) - Lin, Yen-Ting; Tsai, Tzu-Hsiu; Wu, Shang-Gin; Liu, Yi-Nan; Yu, Chong-Jen; Shih, Jin-Yuan
Highlights: Osimertinib is active against lung cancer with activating EGFR mutation and T790M. Its efficacy against complex EGFR mutations with T790M has not been evaluated yet. We found osimertinib response rate was only 27% for complex mutations with T790M. The progression-free survival and overall survival were also significantly shorter. Whether osimertinib is the first choice for this population may be questionable. Abstract: Objectives: Osimertinib is active against epidermal growth factor receptor ( EGFR ) T790M-mutated non-small cell lung cancer (NSCLC). However, its efficacy against complex EGFR mutations with T790M has not been evaluated. Materials and methods: In order to detect complex EGFR mutations, we consecutively sequenced cancer tissues by RNA reverse transcription polymerase chain reaction. Patients with advanced NSCLC with activating EGFR mutation and secondary T790M who received osimertinib were enrolled. Patients' clinicopathologic characteristics, prior treatment details, and osimertinib treatment outcomes were analyzed. Results: Totally, 165 sequenced patients were analyzed. Eleven (7%) of them had complex EGFR mutations with T790M. The osimertinib response rate was 27%. They had a shorter progression-free survival (PFS) (median, 2.9 and 9.7 months, p < 0.001) and overall survival (OS) (median, 17.8 and 31.0 months, p = 0.01) than patients with a single EGFR mutation with T790M. After osimertinib failure, seven patients received rebiopsy with molecular analysis. Four lost the T790M, two transformed to small cell and one acquired C797S. Moreover, taking the median as the demarcation, patients received shorter prior EGFR tyrosine kinase inhibitor (TKI) treatment duration had a shorter osimertinib PFS (median, 7.3 and 13.8 months, p < 0.001) and OS (median, 21.5 and 36.7 months, p = 0.003). Multivariate Cox regression analysis confirmed complex EGFR mutations and prior EGFR TKI treatment duration were independent factors for osimertinib PFS and OS. Conclusions: Complex EGFR mutations and shorter prior EGFR TKI treatment duration may confer shorter osimertinib PFS and OS in advanced NSCLC with secondary T790M mutation.